Rapid Action of Retinoic Acid on the Hypothalamic Pituitary Adrenal Axis - Imoesi, Peter I.; Bowman, Ellen E.; Stoney, Patrick N.; Matz, Sylwia; McCaffery, Peter (Frontiers in Molecular Neuroscience, 2019)
Retinoic acid (RA) is the active metabolite of vitamin A but is also used as a medication, primarily for acne in which the treatment regime lasts several months. A number of studies have indicated that treatment with RA over this time period impacts the hypothalamic-pituitary-adrenal (HPA) axis and may contribute to a number of the side-effects of the drug. No studies though have investigated the short-term, early effects RA may have on the HPA axis via the transcriptional pathways activated by the RA receptor. This study investigated the action of RA over 3 days on regulatory components of the HPA axis. Several key genes involved in glucocorticoid feedback pathways in the hippocampus, hypothalamus and pituitary were unchanged after 3-days exposure to RA. Key elements though in the adrenal gland involved in corticosterone and aldosterone synthesis were altered in particular with the Cyp11b2 gene downregulated in vivo and ex vivo. The rapid, 5 h, change in Cyp11b2 expression suggested this activation may be direct. These results highlight the adrenal gland as a target of short-term action of RA and potentially a trigger component in the mechanisms by which the long-term adverse effects of RA treatment occur.